DEVELOPING AN ENGLISH SUBJECT SYLLABUS FOR CHEMISTRY STUDENTS : a Survey at a State University in Bandung - Nugraha, Andrie Sukma (2013)
The present study aimed to identify the English needs of the chemistry students and propose a syllabus that is expected to meet the needs of the students. A descriptive method was employed to describe information gathered through needs analysis. The data were gathered through a questionnaire distributed to 14 students in pre-service education and interviews with 4 students in pre-service education, 4 alumni, 2 faculty members, the course coordinator, and the English Instructor. The results show that the chemistry education students need to develop their speaking and writing skills in English for the purpose of teaching chemistry. Information from needs analysis including information of the environment, the wanted and necessary skills in English, activities, materials, and assessment became the basis in developing a proposed syllabus consisting of the course rationale, goals, objectives, syllabus, learning activities, materials, assessment, and program evaluation.